THE EFFECT OF ACCOUNTABILITY, TRANSPARENCY, AND QUALITY OF HUMAN RESOURCES ON THE EFFECTIVENESS OF VILLAGE FUND FINANCIAL MANAGEMENT WITH INDIVIDUAL MORALITY AS A MODERATION VARIABLE - Adam Pratama Ibrahim; Neni Nurhayati (Universitas Kuningan, 2025)
This study examines how accountability, transparency, and the quality of human resources influence the effectiveness of village fund financial management, with individual morality as a moderating variable. A quantitative approach was used, involving 291 village officials from Kuningan Regency. Data were collected through questionnaires and analyzed using Moderated Regression Analysis (MRA). The results show that accountability, transparency, and human resource quality significantly affect financial management effectiveness. However, individual morality does not moderate these relationships. These findings highlight the importance of institutional and governance mechanisms over individual traits in optimizing village fund utilization.